Rhizobia inoculation and liming increase cowpea productivity in Maranhão State - Thiago Palhares Farias; Andre Trochmann; Bruno Lima Soares; Fatima Maria Souza Moreira (Acta Scientiarum. Agronomy, 2016)
The objetives of the study were to evaluate the agronomic efficiency of strains approved as inoculants for cowpea and of three new strains under selection, as well as to evaluate the influence of liming on the symbiosis and productivity. Two field experiments were conducted using cowpea (BRS Guariba) from June to September 2013. In the first experiment, a completely randomized block experimental design was used, with four replicates and seven treatments (INPA03-11B, UFLA03-84, UFLA03-153, UFLA03-154, UFLA03-164 and two controls). In the second experiment, a 7 x 2 factorial design was used, with the above described treatments being the first factor and liming as the second factor. Parameters evaluated were: nodule dry matter, shoot dry matter, shoot N content and accumulation, number of pods per plant, number of seeds per pod, weight of 100 seeds, grain yield and grain N content and accumulation. Strains UFLA03-153 and UFLA03-164 were more efficient for cowpea inoculation than the strains approved as inoculants, UFLA03-84 and INPA03-11B. Although the tested rhizobia strains and cultivar BRS Guariba are tolerant to soil acidity, productivity washigher when soil was limed. Yields obtained with fertilized and inoculated treatments were well above Maranhão state average.